Dispersion of adeleid oocysts by vertebrates in Gran Canaria, Spain: report and literature review. Issue 13 (12th November 2021) - Santana-Hernández, Kevin M.; Priestnall, Simon L.; Modrý, David; Rodríguez-Ponce, Eligia
Abstract: Abstract: Within the family Adeleidae, Adelina spp. belong to a group of arthropod pathogens. These parasites have been reported to have a wide geographic distribution, however, there are no reports of these protists in the Canary Islands, Spain. One of the peculiarities of the life cycle of Adelina spp. is the participation of a predator, because fecundation and sporulation occur inside the body cavity, and so necessitate destruction of the definitive host. The involvement therefore of a 'dispersion host', which eats the definitive host and spreads the oocysts through its faeces, is critical for the maintenance of certain Adelina spp. On the island of Gran Canaria, adeleid oocysts have been found in stool samples from four animals, three California kingsnakes ( Lampropeltis californiae ), and one feral cat. These animals were part of a larger coprological study of vertebrate parasites (117 snakes, 298 cats), where pseudoparasitic elements were also recorded. L. californiae and feral cats are invasive species which are widespread across the island and this novel finding of Adelina spp. oocysts in their faeces suggests that they could also serve as potential sentinel species for arthropod parasites.